The complete mitochondrial genome of Scatophagus argus (Perciformes, Scatophagidae) from Beibu Bay and phylogenetic analysis. Issue 9 (2nd September 2021) - Pan, Chuanyan; Gao, Chongmin; Chen, Tao; Yang, Chunling; Zeng, Digang; Feng, Pengfei; Jiang, Weiming; Chen, Xiuli; Peng, Min
Abstract: The spotted scat ( Scatophagus argus, Linnaeus, 1766) is a subtropical fish that is widely distributed in the coastal waters of Indo-Pacific. Here, we report the complete mitochondrial genome of S. argus . The mitogenome is 16, 783 base pairs (56.0% A + T content) in length and consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and a 1007 bp D-loop region. Phylogenetic analysis showed that the relationship between S. argus and Selenotoca multifasciata was close.